The effect of ultrasound on synthesis and energy storage mechanism of Ti3C2Tx MXene - Wu Zhang; Xinyue Zhang (Ultrasonics Sonochemistry, 2022)
Removal of aluminum (abbreviated to Al) accounts for the main step for synthesizing Ti3C2Tx MXene. To date, the synthesis of Ti3C2Tx MXene is hampered by the low removal efficiency of Al from Ti3AlC2. Ultrasound was therefore introduced to achieve efficient synthesis of Ti3C2Tx MXene by promoting the removal rate of Al from Ti3AlC2. It was found that ultrasonic aid can significantly boost the removal efficiency of Al. Additionally, distinct kinetics for the removal of Al was recognized as the advent of ultrasonic intervention: (i) the shrinking core model was used to describe the removal kinetics of Al in the case without ultrasound, whilst the shrinking particle model was capable for the case in presence of ultrasound; (ii) the activation energy for removal of Al with ultrasonic aid was 70.2 kJ/mol, indicating a chemical reaction-controlled process, whereas the corresponding value for the case without sonication was 28.1 kJ/mol, demonstrating a mixed kinetic feature of the removal process of Al. Morphological study showed that ultrasound can remove the surface-adhering reaction products and favors the formation of structures with flower-like morphology. The sample without sonication treatment exhibited typical capacitive behavior, whilst the contribution of diffusion-limited capacitance in addition to the capacitive behavior was readily observed for the sonication-treated sample. Surface chemistry study indicated the more prevalent oxidation of the sonication treated sample, which gave rise to a higher specific capacitance than those without sonication treatment.